Should botulinum toxin a injections be repeated in children with cerebral palsy? A systematic review - Kahraman, Aysu; Seyhan, Kübra; Değer, Ünal; Kutlutürk, Seval; Mutlu, Akmer (Wiley, 2016)
AimThe aim of this study was to determine the effects of repeat botulinum toxin A (BoNT-A) injections in children with spastic cerebral palsy (CP) on the basis of a best evidence synthesis. MethodThis study included 13 original articles after searching the literature to retrieve information. We used the critical review form produced by McMaster University to determine the methodological quality of the studies, and then confirmed the levels of evidence from Sackett. The studies were also evaluated using the International Classification of Function, Disability and Health - Children and Youth Version (ICF-CY). ResultsA total of 893 children with spastic CP who had been administered repeat BoNT-A injections were evaluated. The evidence level was II in four of the thirteen studies, III in four studies, and IV in five studies. The McMaster review form score was 14 in two studies, 13 in four studies, and 12 in seven studies. The results showed that repeat BoNT-A may be a safe and an effective approach. The first two injections/one repeat especially relieve spasticity and improve fine and gross motor activities. InterpretationFuture studies to investigate the effectiveness of repeat BoNT-A in children with spastic CP may be planned within the framework of the ICF-CY to include well-designed randomized controlled trials and those conducted on larger homogenous groups.
WOS: 000382852000011
PubMed ID: 27103334
Keywords: Botulinum Toxin; Children With Cerebral Palsy; Repeated